Glucose(xylose) isomerase production by Streptomyces sp. CH7 grown on agricultural residues - Chanitnun, Kankiya (Sociedade Brasileira de Microbiologia, 2012)
Streptomyces sp. CH7 was found to efficiently produce glucose(xylose) isomerase when grown on either xylan or agricultural residues. This strain produced a glucose(xylose) isomerase activity of roughly 1.8 U/mg of protein when it was grown in medium containing 1% xylose as a carbon source. Maximal enzymatic activities of about 5 and 3 U/mg were obtained when 1% xylan and 2.5% corn husks were used, respectively. The enzyme was purified from a mycelial extract to 16-fold purity with only two consecutive column chromatography steps using Macro-prep DEAE and Sephacryl-300, respectively. The approximate molecular weight of the purified enzyme is 170 kDa, and it has four identical subunits of 43.6 kDa as estimated by SDS-PAGE. Its K(m) values for glucose and xylose were found to be 258.96 and 82.77 mM, respectively, and its V(max) values are 32.42 and 63.64 μM/min/mg, respectively. The purified enzyme is optimally active at 85°C and pH 7.0. It is stable at pH 5.5–8.5 and at temperatures up to 60°C after 30 min. These findings indicate that glucose(xylose) isomerase from Streptomyces sp. CH7 has the potential for industrial applications, especially for high-fructose syrup production and bioethanol fermentation from hemicellulosic hydrolysates by Saccharomyces cerevisiae.